Campi Flegrei, Vesuvius and Ischia Seismicity in the Context of the Neapolitan Volcanic Area - Giudicepietro, Flora; Ricciolino, Patrizia; Bianco, Francesca; Caliro, Stefano; Cubellis, Elena; D’Auria, Luca; De Cesare, Walter; De Martino, Prospero; Esposito, Antonietta M.; Galluzzo, Danilo; Macedonio, Giovanni; Lo Bascio, Domenico; et al. (Frontiers in Earth Science, 2021)
Studying seismicity in a volcanic environment provides important information on the state of activity of volcanoes. The seismicity of the Neapolitan volcanoes, Campi Flegrei, Vesuvius, and Ischia, shows distinctive characteristics for each volcano, covering a wide range of volcanic seismicity patterns and types. In this study we relocated some significant volcano-tectonic (VT) earthquake swarms that occurred in Campi Flegrei and Vesuvius. Moreover, we compared the earthquake occurrence evolution, the magnitude and the seismic energy release of the three volcanoes. Also, we considered the results of seismic analysis in the light of geochemical and ground deformation data that contribute to defining the state of activity of volcanoes. In Campi Flegrei, which is experiencing a long term unrest, we identified a seismogenic structure at shallow depth in Pisciarelli zone that has been activated repeatedly. The increasing seismicity accompanies an escalation of the hydrothermal activity and a ground uplift phase. Even at Vesuvius a very shallow seismicity is recorded, which in recent years has shown an increase in terms of the number of events per year. Earthquakes are usually located right beneath the crater axis. They are concentrated in a volume affected by the hydrothermal system of Vesuvius. Finally, Ischia generally shows a low level of seismicity, however, in Casamicciola area events with a moderate magnitude can occur which are potentially capable of causing severe damage to the town and population, due to their small hypocentral depth (typically<2.5 km). After the seismic crisis of August 21, 2017 (mainshock magnitude M=4), the seismicity returned to a low level in terms of occurrence rate and magnitude of earthquakes. The seismicity of these three different volcanic areas shows some common aspects that highlight a relevant role of hydrothermal processes in the seismogenesis of volcanic areas. However, while the main swarms in Campi Flegrei and most of the Vesuvian earthquakes are distributed along conduit-like structures, the seismicity of Ischia is mainly located along faults. Furthermore, the temporal evolution of seismicity in Neapolitan volcanic area suggests a concomitant increase in the occurrence of earthquakes both in Campi Flegrei and Vesuvius in recent years.